Charging effect on separation performance of outer vortex type cyclone for submicron particles at different operating parameters. (3rd July 2020) - Zhang, Jianping; Zha, Zhenting; Che, Peng; Ding, Honglei; Pan, Weiguo
Abstract: Eliminating fine particles from flue gas is of vital importance to improve air quality, so an outer vortex type electrocyclone (EC) designed with corona wires was built and used to trap submicron particles. Besides, a mathematical model under multi-field coupling effect was established and the charging effect rule on collection efficiency of submicron particles was revealed by comparing the performance of electrocyclone with cyclone and changing operating conditions. The results indicate that the application of charging effect greatly reduces the escape of submicron particles, making that the collection efficiency in EC is far higher than the one in cyclone. Compared to the cyclone, the ability of charging effect to promote the separation performance of EC increases with the increasing working voltage and the decreasing flue gas velocity and temperature and the trapping performance is better at a higher working voltage, lower flue gas velocity, and lower temperature. Furthermore, for outer vortex type EC, the charging effect is more prominent with the decrease of working voltage, flue gas velocity and temperature. The obtained results were evaluated to provide a reliable guide for designing an outer vortex type EC, thus greatly decreasing the number of tests and effectively reducing the research cost. Highlights: A physical model of outer vortex type cyclone with corona wires was built. A theoretical model with four-field coupling interaction is established. The charging effect on collection efficiency of submicron particles is explored. Charging effect can availably improve the separation performance of cyclone. Charging effect is more prominent at lower voltage, flue velocity, and temperature.